2014
DOI: 10.1038/labinvest.2014.92
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 regulates platelet shedding of CD40L in abdominal sepsis

Abstract: Matrix metalloproteinase-9 (MMP-9) regulates platelet shedding of CD40L in abdominal sepsis. However, the signaling mechanisms controlling sepsis-induced shedding of CD40L from activated platelets remain elusive. Rac1 has been reported to regulate diverse functions in platelets; we hypothesized herein that Rac1 might regulate platelet shedding of CD40L in sepsis. The specific Rac1 inhibitor NSC23766 (N6-[2-[[4-(diethylamino)-1-methylbutyl] amino]-6-methyl-4-pyrimidinyl]-2 methyl-4, 6-quinolinediamine trihydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 55 publications
0
25
1
Order By: Relevance
“…Numerous studies have pointed to a functional role of platelets in regulating pathologic aspects of the inflammatory response in severe infections [10,26,34]. For example, there is evidence in the literature showing that platelets are important for the development of dysfunctional coagulation in sepsis [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have pointed to a functional role of platelets in regulating pathologic aspects of the inflammatory response in severe infections [10,26,34]. For example, there is evidence in the literature showing that platelets are important for the development of dysfunctional coagulation in sepsis [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence in the literature showing that platelets are important for the development of dysfunctional coagulation in sepsis [35]. Moreover, accumulating evidence has demonstrated that platelets are potent regulators of neutrophil accumulation in septic lung damage [10,26]. One apparent key mechanism is secretion of potent proinflammatory mediators, such as CD40L, harboring in platelets [10,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower concentrations and shorter exposure, cytotoxicity appeared to be remarkably low. Although cytotoxicity of both inhibitors may be additionally relevant in non-prostatic cells and may limit clinical use, NSC23766 and EHT1864 have been recently applied repeatedly in animal models, where no severe side effects became apparent (Desire et al, 2005;Kawarazaki et al, 2012;Zhang et al, 2013;Hwaiz et al, 2014;Liao et al, 2014;Yoshida et al, 2014).…”
Section: Figurementioning
confidence: 99%
“…Accumulating data suggest that platelets promote pathological inflammation in sepsis (Asaduzzaman et al, 2009;Hwaiz et al, 2014Hwaiz et al, , 2015Rahman et al, 2009). In the present study, it was observed that platelet depletion not only reduced CLP-induced pulmonary levels of MPO but also attenuated lung levels of CXCL2…”
Section: Discussionmentioning
confidence: 99%